2023
DOI: 10.3390/su15065108
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correlation Network Structure of Carbon Emission Efficiency in China’s Construction Industry and Its Formation Mechanism

Abstract: In the context of “carbon peak, carbon neutrality”, it is important to explore the spatial correlation network of carbon emission efficiency in the construction industry and its formation mechanism to promote regional synergistic carbon emission reduction. This paper analyzes the spatial correlation network of carbon emission efficiency in China’s construction industry and its formation mechanism through the use of the global super-efficiency EBM model, social network analysis, and QAP model. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Thirdly, in terms of the regional agricultural carbon emission efficiency spatial correlation network, many scholars have now not only analyzed the differences in agricultural carbon emission efficiency between different regions but also studied in depth the spatial aggregation and convergence of agricultural carbon emission efficiency and other issues involving the spatial correlation network of regional agricultural carbon emission efficiency. In this regard, scholars have conducted extensive studies [37][38][39][40] exploring spatial spillover effects, spatial correlation relationships, etc. Studies have shown that agricultural carbon emission efficiency exhibits significant spatial autocorrelation, and there is a mutual influence relationship between agricultural carbon emission efficiency in different regions.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Thirdly, in terms of the regional agricultural carbon emission efficiency spatial correlation network, many scholars have now not only analyzed the differences in agricultural carbon emission efficiency between different regions but also studied in depth the spatial aggregation and convergence of agricultural carbon emission efficiency and other issues involving the spatial correlation network of regional agricultural carbon emission efficiency. In this regard, scholars have conducted extensive studies [37][38][39][40] exploring spatial spillover effects, spatial correlation relationships, etc. Studies have shown that agricultural carbon emission efficiency exhibits significant spatial autocorrelation, and there is a mutual influence relationship between agricultural carbon emission efficiency in different regions.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Existing research on carbon emissions from buildings mainly focuses on carbon emission measurement [4,5], peak prediction [6], spatial correlation effect [7], and analysis of influencing factors [8,9]. Scholars measure the carbon emissions of each region based on the LCA theory [10,11], IPCC [12], MFA [13], etc., to further predict the peak situation through scenarios and models such as LEAP [14].…”
Section: Introductionmentioning
confidence: 99%